Evaluasi Butir Soal Pilihan Ganda Penilaian Tengah Semester dalam Pembelajaran Tematik untuk Kelas V di SDN Gladak Anyar 4 Pamekasan - Ria Kasanova; Roni Sulistiyono (Departement of Mathematics Education, 2023)
This research was conducted with the aim of evaluating the validity, level of difficulty, discriminating power, effectiveness of the distractor, and reliability of multiple choice questions in the Mid Semester Assessment in fifth grade thematic learning at SDN Gladak Anyar 4 Pamekasan. The research method used is a quantitative descriptive approach. There are two themes in the Mid Semester Examination Questions, namely theme 6 with 20 questions and theme 7 with 19 questions. Evaluation of the validity of the questions, level of difficulty, discriminating power, effectiveness of the distractor, and reliability was carried out using Microsoft Excel 2010. The subjects of this study were fifth grade students, and data collection was carried out using documentation techniques. The results of this study indicate that the quality of the questions is high. (1) The validity of the questions in theme 6 were 19 questions (95%) and in theme 7 were 18 questions (94.74%) declared valid. (2) The difficulty level of the questions in theme 6 consisted of 13 questions (68.42%) which were categorized as easy and 2 questions (10.53%) which were categorized as difficult. In theme 7, there are 11 questions (61.11%) which are categorized as easy, so there are questions with difficulty levels that do not meet good quality. (3) The discriminating power of questions on theme 6 consisted of 10 items (52.63%) which were categorized as poor and 1 item (5.26%) which were categorized as good. In theme 7, there are 6 items (33.33%) which are categorized as not good and 3 items (16.67%) which are categorized as good. Therefore, the questions fall into the category of moderate discriminating power. (4) The effectiveness of the distractor in theme 6 consisted of 1 item (5.26%) which was categorized as very good, 8 items (42.11%) which were categorized as good, and 6 items (31.58%) which were categorized as poor. In theme 7, there were 4 items (22.22%) which were categorized as very good, 4 items (22.22%) which were categorized as good, and 3 items (16.67%) which were categorized as poor. Thus, the questions fall into the category of the effectiveness of a good distractor. (5) The reliability of the questions in theme 6 is 0.9592, while in theme 7 it is 0.8950, indicating that the questions have high reliability and high quality.